2004
DOI: 10.14214/sf.439
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril angle and density patterns of fertilized and irrigated Norway spruce

Abstract: Two Norway spruce nutrient optimisation trials, one in the north of Sweden and one in the south, were used to study the effects of intensive growth and fertilization on wood density and microfibril angle. Three different treatments and a control were available; daily irrigation, daily liquid fertilization and solid fertilization. The nutrient optimisation was based on foliage analysis and the solid fertilization essentially comprised the same amount of nutrients but was applied annually in solid form. Measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…This is because of the fact that agricultural land usually contains a greater quantity (usually artificially supplied) of nutrients that result in a faster growth, which is reflected in the larger annual ring width, and thus for conifers, it is accompanied by a decrease in the density of such wood. This fact is confirmed by studies evaluating the effect of artificial fertilization of forest growth (analogy of nutrient delivery to agricultural crops) on wood properties, where it is clearly demonstrated that higher nutrient intake corresponds to a decrease in density and strength of the spruce, pine or the Douglas fir [34][35][36]. However, this may not be the norm, as proven by Bartoš [20] for spruce wood in the Czech Republic, and wood from such sites need not be regarded as less valuable.…”
Section: Discussionmentioning
confidence: 70%
“…This is because of the fact that agricultural land usually contains a greater quantity (usually artificially supplied) of nutrients that result in a faster growth, which is reflected in the larger annual ring width, and thus for conifers, it is accompanied by a decrease in the density of such wood. This fact is confirmed by studies evaluating the effect of artificial fertilization of forest growth (analogy of nutrient delivery to agricultural crops) on wood properties, where it is clearly demonstrated that higher nutrient intake corresponds to a decrease in density and strength of the spruce, pine or the Douglas fir [34][35][36]. However, this may not be the norm, as proven by Bartoš [20] for spruce wood in the Czech Republic, and wood from such sites need not be regarded as less valuable.…”
Section: Discussionmentioning
confidence: 70%
“…At an interannual scale, wood density variations can be substantial. There were several reports that (annual) ring density decreases with increasing ring width, for instance in Norway spruce (Bergqvist, 1998;Dutilleul et al, 1998;Lundgren, 2004;Bouriaud et al, 2005;Franceschini et al, 2010Franceschini et al, , 2013. Wood density was also proved to vary between trees (Wilhelmsson et al, 2002;Guilley et al, 2004), a fact which is never accounted for in studies using diameter surveys to produce biomass increment estimations.…”
Section: O Bouriaud Et Al: Influence Of Wood Density On Productivitymentioning
confidence: 99%
“…(Yang and Evans 2003), Picea abies (L.) Karst. (Lundgren 2004, Piispanen et al 2014, Pinus taeda L. (Jordan et al 2005), Pseudotsuga menziesii (Mirb.) Franco (Vikram et al 2011), Pinus sylvestris L. (Auty et al 2013) and Pinus radiata D.Don (Ivković et al 2013).…”
Section: Introductionmentioning
confidence: 99%